A Retrospective Study on the Adverse Effects of Chemotherapy in Breast Cancer-A Multicenter Study - Kodati, Devender; Tirumala, Sowmya; Kantheti, Rishitha Krishna; Reddy Thumma, Joseph Priyatham (Indian Journal of Pharmacy Practice)
Objective: The present study is a retrospective observational and a non-comparative descriptive study, to evaluate the clinical manifestations, risk factors, diagnosis, treatment regimen and mainly the adverse effects associated with the chemotherapeutic drugs, where the case sheets of the breast cancer patients were reviewed properly and the required data is obtained and finding of adverse effects was considered as the primary parameters. Methodology: A total of 353 patients were enrolled in the study. The required demographic details and laboratory data were reviewed from the case sheets. During chemotherapy, some of the patients were given with AC, T (Doxorubicin, cyclophosphamide, paclitaxel) regimen and few patients were given with CAF (Cyclophosphamide, Doxorubicin, 5-FU) regimen. The reports were re-reviewed for adverse effects after chemotherapy. Results: Among 353 patients, 344 patients have shown adverse effects and 9 patients were without any adverse effects during chemotherapy. We have identified 1,157 adverse effects in a total of 344 patients, among them 16.5% were found to be cardiac effects, 60.5% were found to be haematological effects and 22.6% were found to be in USG abdomen. Conclusion: Among 353 patients, age group between 49-58 years has shown higher adverse effects (25.85%) and the least adverse effects were presented by the age group between 18-28 years (6.52%).
Keywords: Breast cancer; Chemotherapy; Adverse effects; Doxorubicin; Cyclophosphamide; Paclitaxel.